PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA MANAJERIAL PT. BANK SUMUT - Hadi Pramono; Isfenti Sadalia Lubis; Arlina Nurbaity Lubis (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2015)
The objective of the research is to find out and to analyze the influence of intellectual capitalwhich consists of customer capital, human capital, and structural capital simultaneously on themanagerial performance of PT. Bank SUMUT, the influence of the variables of customer capital,human capital, and structural capital partially on the managerial performance of PT. Bank SUMUT,and to find out the intellectual capital which consists of customer capital, human capital, andstructural capital from the financial-ratio perspective of PT. Bank SUMUT. The research method usedis a survey approach. The research type is a quantitative descriptive and the characteristic is anexplanatory descriptive. Data collecting method is done by providing a list of written questions anddocumentation study. Data analyzing method used is the multiple- linear regression and SPSS software.The result of descriptive-statistical analysis shows that intellectual capital which consists of customercapital, human capital, and structural capital and the managerial performance of PT. Bank SUMUT iscategorized very agreeable and each variable tested is normally distributed. The simultaneous-researchresult shows the intellectual capital which consists of customer capital, human capital, and structuralcapital influence positively and significantly the managerial performance of PT. Bank SUMUT. Thepartial- research result shows the variables of customer capital, human capital, and structural capitalinfluence positively and significantly the managerial performance of PT. Bank SUMUT. The financialratioperspective shows it is in line with the managerial performance of PT. Bank SUMUT. Thedeterminant coefficient value (adjusted R square) is 82.2% which means that the ability of customercapital, human capital, and structural capital can describe the variation of managerial performance ofPT. Bank SUMUT, and the remaining 17.8% is influenced by other variables excluded from theanalysis.Keywords: Intellectual Capital, Customer Capital, Human Capital, Structural Capital, ManagerialPerformance